Strengthening self-confidence of students with visual impairment through STAD and Jigsaw: A case study in inclusive lectures - Zulfa Rahmah Effendi; Fajar Indra Septiana; Prinanda Gustarina Ridwan; Aini Qurrotullain (Curricula: Journal of Curriculum Development, 2025)
The application of cooperative learning for students with visual impairments in lectures focusing on behavior modification of children with special needs has been rarely studied in depth. Therefore, this study investigates the impact of cooperative learning on the self-confidence of students with visual impairments in the Behavior Modification of Children with Disabilities course. The study employed a qualitative case study design involving two students with low vision and six regular students as supporting informants. The Student Teams Achievement Divisions (STAD) and Jigsaw cooperative learning types were applied for six meetings. Data were collected through observation, in-depth interviews, and documentation, and analyzed thematically. The results demonstrate that cooperative learning can foster an inclusive environment that enhances the self-confidence of students with visual impairments. This is evident in their increased active participation and courage in interacting with classmates and lecturers. The main supportive factors are empathy from classmates and positive reinforcement from lecturers. However, there are also inhibiting factors: internal anxiety, which impacts self-confidence, and a lack of understanding from the surrounding environment about the impact of visual impairment on students with visual impairments.   Abstrak Penerapan pembelajaran kooperatif khususnya bagi mahasiswa dengan gangguan penglihatan dalam konteks perkuliahan yang berfokus pada modifikasi perilaku Anak Berkebutuhan Khusus (ABK) masih jarang dikaji secara mendalam. Maka dari itu, penelitian ini bertujuan mengkaji pembangunan kepercayaan diri mahasiswa dengan gangguan penglihatan melalui pembelajaran kooperatif dalam perkuliahan Modifikasi Perilaku ABK. Metode penelitian yang digunakan adalah kualitatif dengan desain studi kasus yang melibatkan dua mahasiswa dengan gangguan penglihatan kategori low vision dan enam mahasiswa awas (reguler) sebagai informan pendukung. Pembelajaran kooperatif tipe Student Teams Achievement Divisions (STAD) dan Jigsaw diterapkan selama enam pertemuan. Data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi, kemudian dianalisis secara terperinci dan tematik. Hasil menunjukkan bahwa pembelajaran kooperatif dapat menciptakan lingkungan inklusif yang mendukung peningkatan kepercayaan diri mahasiswa dengan gangguan penglihatan. Hal itu terlihat dari adanya peningkatan partisipasi aktif dan keberanian dalam berinteraksi dengan teman sekelas dan dosen. Faktor pendukung utama adalah rasa empati yang diberikan oleh teman sekelas dan penguatan positif yang dilakukan oleh dosen, namun disisi lain terdapat faktor penghambat yaitu kecemasan internal yang berdampak pada rasa percaya dirinya dan kurangnya pemahaman dari lingkungan sekitar mengenai dampak gangguan penglihatan pada kemampuan belajar mahasiswa low vision. Kata Kunci: gangguan penglihatan; kepercayaan diri; pembelajaran kooperatif; pendidikan inklusif